Readings in the economics of taxation - American Economic Association; Musgrave, Richard Abel (London George Allen & Unwin Ltd, 1959)
This selection of readings is an intensive treatment of a part of the field of public finance - taxation. It was chosen on the grounds that it would be of more lasting value to the research worker and teacher, while the area could be so delimited that editors of subsequent readings in public finance would not find it difficult to avoid overlapping, or gaps.
Includes bibliographical references.
osc 10/12/2018
Loans
Keywords: Taxation